An optimized observer for estimating torque converter characteristics for vehicles with automatic transmission - J, Niresh; R, Kirubakaran; M, Mohana Praddeesh; V, Gokul; T, Gokkul (International Journal of Engineering and Technology, 2018)
The trending technology in the automobile power train system is the automatic transmission which allows the driver to drive the vehicle without pressing the clutch and can make gear shifting decisions themselves and thus frees the driver from shifting the gears manually. The system consists of torque convertor which replaces clutch and an alternate transmission system which consisting of planetary gears and actuators as drivetrain. In spite of the advantages of the automatic transmission system, there is a problem developing a controller for the system. That is because of the fact that the parameters characterizing the performance of the power train are not measurable because of sensor cost and reliability considerations. There is a need to provide real time information about the un-measurable parameters especially the internal state parameters of the torque converter. Thus, this paves the way for the development of model-based estimation for automatic transmission system to improve the fuel economy during the whole driving profile. The state space analysis can aid in the process. Several outputs from the system can be measured and can be used as a model for observing the internal states of the torque converter system. For this analysis MATLAB/Simulink can be used to model the plant and tools available in MATLAB can aid in developing a specific â€œstate observerâ€ which is the means in which the states can be studied.